Qualitative Analysis of Multicultural Culture in the Code of Ethics and Global Unilever Annual Report 2024 - Cindy Fionna; Badariah Lestari; Afrini Ramayanti; Dian Prihardini Wibawa (Universitas KH. Abdul Chalim Mojokerto, 2026)
Global business expansion puts corporate companies in a challenging position in aligning organizational policies with different backgrounds in operational areas. This study analyzes the existence of a multicultural cultural integration strategy through secondary data from the Code of Business Principles document and the Annual Report and Accounts for 2024. Using descriptive qualitative analysis methods, and triangulation of data and sources, three main findings were obtained: (1) Gender representation as much as 44% of global legitimacy inclusivity; (2) Adaptation of global and local cultural dimensions through respect for customary rights and lands; and (3) The implementation of the Speak Up system and reporting to mitigate ethical risks and also Power Distance. This research confirms that global ethical standardization and governance transparency not only improve the psychological safety of employees, but strengthen investor trust and improve the company's image in a sustainable manner.